Social Media Use, Adolescent Emotion Regulation Factors, and Islamic Counseling Constructs: A Systematic Literature Review - Mursidin Mursidin; Gattan Rafani Azzam; Muhammad Zikri Salihima; Muhammad Fadly Nuril Arsy (Universitas Hamzanwadi, 2026)
This study presents a systematic literature review of recent scientific evidence on the relationship between social media use and adolescent emotion regulation. It also identifies the factors that shape this relationship and proposes Islamic counseling as a conceptual framework for promoting healthy digital behavior. The review followed the PRISMA 2020 guidelines and examined Scopus-indexed publications published between 2021 and 2026. The literature search used two primary keyword combinations: “social media emotion regulation adolescents” and “adolescent emotion regulation social media,” supported by Boolean combinations related to social media, digital media, emotion regulation, emotion dysregulation, and adolescents. From 608 initial records, 171 duplicates, 93 articles outside the publication period, 67 articles published in journals outside Q1–Q3 categories, and 15 articles without abstracts were excluded. Following title and abstract screening, 187 articles were removed, while 22 reports could not be retrieved. A total of 53 studies were included in the final narrative-thematic synthesis. The findings indicate that social media is associated with adolescent emotion regulation through communication, self-expression, social support, self-validation, identity formation, social comparison, and emotional coping. This relationship is influenced by self-control, impulsivity, emotional intelligence, body esteem, family support, peer pressure, cyberbullying, fear of missing out, platform algorithms, and mental health conditions. Islamic counseling can be conceptualized through self-reflection, self-purification, patience, self-control, self-acceptance, digital ethics, moral responsibility, relational support, and inner peace. This review contributes to the development of Islamic guidance and counseling by providing a value-based conceptual response to adolescents’ emotional challenges in digital environments.